Spinal Cord Ischemia Secondary to Hypovolemic Shock - Jacob YL Oh; Siddhant Kapoor; Roy KM Koh; Eugene WR Yang; Hwan-Tak Hee (Asian Spine Journal, 2014)
A 44-year-old male presented with symptoms of spinal cord compression secondary to metastatic prostate cancer. An urgent decompression at the cervical-thoracic region was performed, and there were no complications intraoperatively. Three hours postoperatively, the patient developed acute bilateral lower-limb paralysis (motor grade 0). Clinically, he was in class 3 hypovolemic shock. An urgent magnetic resonance imaging (MRI) was performed, showing no epidural hematoma. He was managed aggressively with medical therapy to improve his spinal cord perfusion. The patient improved significantly, and after one week, he was able to regain most of his motor functions. Although not commonly reported, spinal cord ischemia post-surgery should be recognized early, especially in the presence of hypovolemic shock. MRI should be performed to exclude other potential causes of compression. Spinal cord ischemia needs to be managed aggressively with medical treatment to improve spinal cord perfusion. The prognosis depends on the severity of deficits, and is usually favorable.